Kriya Gerabah Bumi Jaya : Pendidikan Keluarga Pada Perajin Gerabah Bumi Jaya (Catharsis, 2022)
The purpose of this study is to examine the efforts made by craftsmen to maintain traditional crafts. By using a qualitative descriptive method. This study uses an interdisciplinary approach that includes ethnography to examine culture in society, and education. From the results of data and information collection and analysis, it can be seen that in Indonesian culture there are many things that must be preserved, both traditional and artistic, such as what the Bumi Jaya people do to maintain traditional crafts in Banten. In this era of globalization, traditional arts experience stagnant times to continue to survive and be recognized, many efforts can be made by craftsmen to maintain traditional crafts. Like what Bumi Jaya craftsmen do to maintain their pottery, where Bumi Jaya pottery has been known since the sultanate period which will then come to the next generation so that it can be said as a traditional art. Bumi Jaya craftsmen continue to try to maintain traditional pottery crafts in various ways, one of which is in the family environment, craftsmen pass it on to the next generation through daily activities that involve children when the pottery-making process, which is called family education, parents play an important role in family education, This family education aims to reduce pottery making skills and teach the v alues ​​of life such as caring and kinship. Kata kunci : tembikar, Bumi Jaya, seni